Selected collocations in English: contributions to Business English fluency - Fanha Martins, Hélder (2017)
The collocations in this text have been selected to make it as useful and easy to use as possible for learners of English. A special effort has been made to identify and incorporate collocations that are used in the business area, thus, contributing to a better business English fluency. The collocations presented here were selected from those identified as significant from multiple sources: The CANCODE Corpus of Spoken English, The Cambridge International Corpus of Written and Spoken English, The Cambridge Learner Corpus, the British National Corpus, the BBI Dictionary of English Word Combinations, the Collins COBUILD English Dictionary, the Oxford Advanced Learner’s Dictionary, the Oxford Dictionary of English Idioms, the Longman Dictionary of English Collocations, and Tom Cobb’s LexTutor Concordance System (http://www.lextutor.ca/).